Association between gut microbiota and primary ovarian insufficiency: a bidirectional two-sample Mendelian randomization study - Wang, Jiahui; Luo, Rong; Zhao, Xia; Xia, Di; Liu, Yi; Shen, Tao; Liang, Yuanjiao (Frontiers in Endocrinology, 2023)
Recent studies have indicated a potential correlation between intestinal bacteria and primary ovarian insufficiency (POI). However, the causal relationship between the gut microbiota (GM) and POI remains unclear. A bidirectional two-sample Mendelian randomization (MR) study was conducted to investigate the relationship between the GM and POI. GM data were based on the MiBioGen consortium's summary statistics from the most comprehensive genome-wide association study meta-analysis to date (n=13,266), and POI data were obtained from the R8 release of the FinnGen consortium, containing a total of 424 cases and 181,796 controls. Various analytical methods, including inverse variance weighting, maximum likelihood, MR-Egger, weighted median, weighted model, MR-pleiotropy residual sum and outlier (PRESSO), constrained maximum likelihood and model averaging, and Bayesian information criterion, were utilized to explore the connection between the GM and POI. Cochran's Q statistics were used to evaluate the heterogeneity of the instrumental variables. The MR-Egger and MR-PRESSO methods were used to identify the horizontal pleiotropy of instrumental variables. The MR Steiger test was used to evaluate the strength of causal relationships. A reverse MR study was performed to investigate GMs that were indicated to have a causal relationship with POI in a previous MR evaluation. The inverse variance weighted analysis indicated that Eubacterium hallii (odds ratio [OR]=0.49, 95% confidence interval [CI]: 0.26–0.9, P=0.022) and Eubacterium ventriosum (OR=0.51, 95% CI: 0.27–0.97, P=0.04) had protective effects on POI, whereas Intestinibacter (OR=1.82, 95% CI: 1.04–3.2, P=0.037) and Terrisporobacter (OR=2.47, 95% CI:1.14–5.36, P=0.022) had detrimental effects on POI. The reverse MR analysis revealed that POI had no significant influence on the four GMs. No significant heterogeneity or horizontal pleiotropy was observed in the instrumental variables. This bidirectional two-sample MR study revealed a causal link between Eubacterium (hallii group), Eubacterium (ventriosum group), Intestinibacter, and Terrisporobacter and POI. Additional clinical trials are required to elucidate the beneficial and detrimental effects of GMs on POI and their mechanisms of action.